Pengaruh waktu aplikasi dan konsentrasi penambahan sari buah jambu biji merah (Psidium guajava L.) terhadap kefir susu kambing - Wiwik Endah Rahayu; Siti Halimatu Sa’diyah; Atika Romalasari (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Red guava is generally processed into fruit juice. Fruit juice can be used as an additional ingredient in making goat milk kefir to increase public interest in goat milk. The purpose of this study was to determine the effect of application time and concentration of addition of red guava juice on levels of TAT, vitamin C, pH and hedonic kefir test. The research method used completely randomized design (CRD) with 4 treatments 3 replications. The treatments given are giving fruit juice before fermentation with 10% concentration (P1), giving fruit juice before fermentation with 30% concentration (P2), giving fruit juice after fermentation with 10% concentration (P3) and giving fruit juice after fermentation with 30% concentration (P4). Data analysis for TAT, vitamin C, pH and hedonic test parameters analyzed by ANOVA followed by duncan tests. Application time and concentration of addition of red guava juice have a significant effect on TAT, Vitamin C and pH.. Based on the hedonic test results, the combination of adding fruit juice after fermentation with 30% concentration has the highest value with a color test value of 3.55 (like moderately), aroma 2.98 (neither like), a taste of 3.53 (like moderately), thickness of 3.29 (neither like) and overall like 3,6 (like moderately). Addition of juice after fermentation with a concentration of 30% has TAT ​​(1.65%), Vitamin C (94.13 mg) and pH (4.00).